Ferret Hepatitis E Virus Infection in Japan - Li, Tian-Cheng; Yonemitsu, Kenzo; Terada, Yutaka; Takeda, Naokazu; Takaji, Wakita; Maeda, Ken (Japanese Journal of Infectious Diseases, 2015)
We examined 85 fecal samples from pet ferrets in 10 animal hospitals in Japan for the detection of ferret hepatitis E virus (HEV) RNA. We found that 6 (7.1%) of the samples were positive for ferret HEV RNA. Phylogenetic analysis based on the partial ORF1 indicated that these ferret HEV strains were clearly separated from the Netherlands strains and were divided into 2 distinct clusters. These results suggest that ferret HEV is genetically diverse, and since ferrets are not indigenous to Japan, ferret HEV has been introduced into Japan through importation.